Tracking the hacking. (Economist, 2025)
The article discusses the growth of China's hacking program, with Chinese hackers getting better, bigger and stealthier. Topics discussed include the growing sophistication of China which resulted to success in political espionage, industrial-scale theft of intellectual property and hacking which lays the groundwork for sabotage in moments of war or crisis, China's hosting of competition to show the hacking power of competitors, and the shift in the global cyberthreat landscape.